Le tourisme de diaspora en Haïti - Bazelais Dulience (Études Caribéennes)
The Haitian diaspora constitutes a major player in very varied fields such as education, construction and tourism. Its money transfers are more important than official development assistance. The emotional relationship maintained with the country greatly contributes to fuelling tourist flows to this destination despite its general state characterized by the crisis. This attachment is confirmed even in the darkest moments of the country's history. This is the case with political unrest and natural disasters. Some people think that, faced with the Covid-19 pandemic, considering the fragility of the country's health system, the diaspora's relationship with the destination has shown its limits. Thus, this health crisis appears to be a special context allowing us to question, through tourism, this degree of attachment of members of the Haitian community established outside Haiti to the country. The northern region is considered the framework for analysis.